Enhancing Teaching Skills: The Principal's Role in Implementing Convergence Clinical Model for Questioning Skills Improvement: Peningkatan Keterampilan Mengajar: Peran Kepala Sekolah dalam Penerapan Model Klinis Konvergensi untuk Peningkatan Keterampilan Bertanya - Tiyas, Nenin Maining; Murtadlo , Murtadlo; Suparti , Suparti (Pedagogia : Jurnal Pendidikan, 2023)
This study aims to describe holistically the role shown by the principal as a supervisor through supervision activities of the convergence clinical model to improve teacher teaching skills, especially questioning skills. This research uses a qualitative approach with a multi-case study design. The subjects of this research were SDN Dukuhklopo and MI Plus Darul Falah Jombang. Data collection instruments in this study used in-depth interview techniques, participant observation, and documentation studies. Data analysis is carried out together with the process of data collection and analysis after data collection is complete. The results of the study show (1) In planning supervision, the supervision program made by the principal of the school/madrasah includes efforts to improve questioning skills or learning competencies in general that need to be improved. Furthermore, the school principal socializes the supervision program with teachers. (2) Implementation of school/madrasah supervision begins with assessing the completeness of teaching tools and to improve questioning skills, supervisors carry out observations using instruments. (3) The follow-up of school/madrasah supervision is carried out, namely the follow-up on the results of the evaluation of teacher teaching tools and the results of supervision of class visits.